JURISDIKSI AMBIGU DALAM PENGELOLAAN KENAKALAN PESERTA DIDIK: ANALISIS KONFLIK KEWENANGAN ANTARA GURU PAI DAN GURU BK DI SEKOLAH MENENGAH ATAS KABUPATEN JEMBER - Imron Rosady; Dani Hermawn; Nadilla Aleyda Maqhfira Agustin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The management of student delinquency in high schools often falls into a "gray zone" of authority, triggering latent conflicts between two key educational actors: Islamic Education (PAI) teachers and Guidance and Counseling (BK) teachers. Although both professions share the ultimate goal of student character development, their paradigms—religious moral enforcement versus psychological intervention—frequently collide. This study employs a multi-site qualitative case study approach in three public high schools in Jember: SMAN Rambipuji, SMAN Balung, and SMAN Arjasa. The findings reveal that the absence of a comprehensive, written Standard Operating Procedure (SOP) that integrates both perspectives results in ad-hoc conflict resolution. Although disputes are often settled peacefully through dialogue mediated by the principal, the lack of a binding regulation covering the shared interest of the student leads to recurring disputes. This article argues that without a synergistic regulatory framework that clearly delineates yet integrates the roles of PAI and BK, the best interests of the student are often sidelined in favor of bureaucratic territoriality. The study concludes that temporary personal peace agreements are insufficient to resolve structural role ambiguities across different school contexts